The impact of data collection for farmer organisations - Koopman, Martine; Ayim, Claudia (Technical Centre for Agricultural and Rural Cooperation, 2019)
In Uganda, CTA has been working with the Igara Tea Growers Factory (IGTF) to digitally profile their farmer members and enhance their data management practices. In this piece, the impact of these activities for the individual farmers, and the cooperative as a whole, is assessed.